MECHANISMS FOR ENHANCING PROJECT EFFECTIVENESS THROUGH TEAM INTERACTION: A THEORETICAL AND METHODOLOGICAL ANALYSIS - Забурмеха, Євгена; Атаманюк, Руслан (SWorldJournal, 2026)
The article examines the problem of enhancing the effectiveness of project activities under conditions of rapid change and uncertainty in the business environment. It substantiates the proposition that a key factor in project success is the quality of tea